جۆرەكانى نۆستاليژيا وهۆكارەكانى دروستبوونيان - عزيز، سامان جلال; علي، عز الدين صابر محمد علي (جامعة تكريت - كلية التربية للبنات, 2023)
النوستالجيا أو الحنين إلى الماضي هي حالة طبيعية تصيب الكثير من الأشخاص وتشعرهم بالسعادة تجاه ذكريات عاشوها في الماضي، فأغلب الأشخاص الذين يعيشون تحت ضغط وتعب وإرهاق ومشاكل نفسية يشعرون براحة وسعادة عارمة عندما يسرحون ذكريات قديمة من الماضي تذكرهم بقصص وحكايات سعيدة مع أهلهم وأصدقائهم وجيرانهم لأنهم في الغالب يفتقدونها في حينها وغير قادرين على إعادتها بكامل تفاصيلها، لذا تساعدهم النوستالجيا على تغير حالتهم المزاجية والشعور بسعادة عابرة لأنها غالبا ما تكون مؤقتة ويرجعون مرة أخرى لحياتهم الطبيعية. يتكون بحثنا الموسوم (أسباب تكوين نوستالجيا وأنواعه)، يتكون من مقدمة والملخص والنتائج والقائمة والمصادر والمراجع، والملخص باللغة العربية والإنكليزية، يتكون الفصل الأول يتكون من المبحثين، حيث في المبحث الأول تناول البحث أهم المصطلحات والمفاهيم النظرية وكذلك عدة تعاريف لمفهوم نوستالجيا. أما في المبحث الثاني تطرق البحث إلى أنواع نوستالجيا وأهم خصائصه. أما القسم الثاني يتضمن أسباب ظهور نوستالجيا وكذلك أهم فوائد نوستالجيا في الأدب). This study aims to investigate the various types of challenges and limitations at semantic levels that translators face in the business and economic translation products of tenders and bids from English into Arabic. To achieve the objectives of the study, a sample of four tenders of business documents was collected from a variety of national and international non-governmental organizations such as the bilingual specialized texts that were published between 2019 and 2020 in Iraq, specifically in Erbil, Kurdistan Region. The study relies on Holmes’ map (1988) of descriptive translation studies, developed by Toury (1995). To answer the research questions: how does a translator deal with specialised terminologies and expressions in translating business tenders and bids and what effect and role do semantic changes play in business and economic translation products? The study employs the analytical-descriptive translation methodology in analysing business texts. The analysis of business and economic texts has revealed that inaccurate synonyms at the semantic level, such as using different synonyms and translating semantic collocations, appear more frequently than other issues in translating business texts in the target language. The findings of the study have indicated that business and economic terms may have more than one accurate and faithful translation. Nevertheless, one translation can be appropriate and accurate. The study has concluded that cultural phenomena rarely appear in business and economic tenders and bids in comparison with other areas of economic and business texts, e.g., metaphors and idioms in general business texts.
Keywords: الحنين إلى الماضي -- النوستالجيا -- مصطلح "الحنين" -- الأدب الفارسي